On the importance of critical thinking: A response to Wulf's (2015) commentary. (January 2016) - Toner, John; Moran, Aidan
Abstract: In a recent paper (Toner & Moran, 2015 ), we argued that continued improvement among elite athletes requires alternation between external and internal foci of attention. In her commentary on this paper, Wulf (2015) claims that we have misunderstood the 'attentional focus' effect. Our rejoinder has three objectives. Firstly, we critically evaluate Wulf's arguments and counter her false allegations and spurious reasoning. Secondly, we explain our concerns about certain aspects of attentional focusing research. Finally, we propose that in order to explore the dynamic nature of attentional focusing, we need to go beyond restrictive theoretical dichotomies (e.g., "internal" versus "external" processes) using new approaches. Highlights: We counter the false allegations and spurious reasoning evident inWulf's (2015) commentary. We re-iterate a number of our methodological and theoretical concerns about attentional focus research. We consider the need to go beyond restrictive theoretical dichotomies.